Students' and Teachers' Values, Attitudes, Feelings and Beliefs in Mathematics Classrooms Selected Papers from the 22nd MAVI Conference (Springer International Publishing, 2018)
This contributed volume is an exciting product of the 22nd MAVI conference, which presents cutting-edge research on affective issues in teaching and learning math. The teaching and learning of mathematics is highly dependent on students' and teachers' values, attitudes, feelings, beliefs and motivations towards mathematics and mathematics education. These peer-reviewed contributions provide critical insights through their theoretically and methodologically diverse analyses of relevant issues related to affective factors in teaching and learning math and offer new tools and strategies by which to evaluate affective factors in students' and teachers' mathematical activities in the classroom. Among the topics discussed: The relationship between proxies for learning and mathematically related beliefs. Teaching for entrepreneurial and mathematical competences. Prospective teachers' conceptions of the concepts mean, median, and mode. Prospective teachers' approach to reasoning and proof The impact of assessment on students' experiences of mathematics. Through its thematic connections to teacher education, professional development, assessment, entrepreneurial competences, and reasoning and proof, Students' and Teachers' Values, Attitudes, Feelings and Beliefs in Mathematics Classrooms proves to be a valuable resource for educators, practitioners, and students for applications at primary, secondary, and university levels.